Comparison of Aspirin s Antioxidant Effect with Selenium and Vitamin E by Measuring Mitochondrial Selenium Dependent Glutathione Peroxidase and Cytosolic Total Glutathione Peroxidase Activity in Mice Liver - Cebi, Aysegⁿl; Diraman, Emine; Eren, Zafer (Asian Journal of Chemistry, 2010)
In this study, the antioxidant effect of aspirin was studied and compared with selenium and vitamin E on the activities of mitochondrial selenium dependent glutathione peroxidase (Se-GPX) and cytosolic total glutathione peroxidase (t-GPX). After the injection of selenium, vitamin E and aspirin intraperitonally to the mice, they were killed by servical dislocation at the 2, 4, 8, 12 and 24 h and their livers were removed. Enzyme fractions were obtained from livers. Mitochondrial fractions were used to find out the changes in the Se-GPX activities and cytosolic fractions were used to find out the changes in the total GPX activity. Aspirin increased cytosolic t-GPX activity in 12 and 24 h and mitochondrial Se-GPX activity in 8 h when compared with controls (p < 0.05). The t-GPX activity was less than vitamin E in 2 h and selenium in 12 h (p < 0.05). The study shows that aspirin has an antioxidant effect by increasing the cytosolic t-GPX and mitochondrial SeGPX activity. The antioxidant effect of aspirin is less than selenium and vitamin E.